2020
DOI: 10.21105/joss.01987
|View full text |Cite
|
Sign up to set email alerts
|

Hoki: Making BPASS accessible through Python

Abstract: We now know that a large number of stars are born in multiple systems. Additionally, more than 70% of massive stars are found in close binary systems, meaning that they will interact over the course of their lifetime (Sana et al., 2012). This has strong implications for their evolution as well as the transients (e.g supernovae) and the potential gravitational wave progenitors they produce. Therefore, in order to understand and correctly interpret astronomical observations of stellar populations, we must use th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 7 publications
(9 reference statements)
0
34
0
Order By: Relevance
“…14) within 150 pc (10 arcmin) from R136a1 (Walborn 1991) to the population synthesis prediction from BPASS (v.2.2.1, Stanway & Eldridge 2018). We downloaded the commonly used and publicly available BPASS output 3 and visualised it with the python package Hoki which has been designed to interface with the BPASS models and their outputs (Stevance et al 2020). The publicly available BPASS models for binary population synthesis used the binary, period and mass distribution according to Sana et al (2012); Moe & Di Stefano (2017).…”
Section: The Stellar Population Of R136 and The Tarantula Nebulamentioning
confidence: 99%
See 1 more Smart Citation
“…14) within 150 pc (10 arcmin) from R136a1 (Walborn 1991) to the population synthesis prediction from BPASS (v.2.2.1, Stanway & Eldridge 2018). We downloaded the commonly used and publicly available BPASS output 3 and visualised it with the python package Hoki which has been designed to interface with the BPASS models and their outputs (Stevance et al 2020). The publicly available BPASS models for binary population synthesis used the binary, period and mass distribution according to Sana et al (2012); Moe & Di Stefano (2017).…”
Section: The Stellar Population Of R136 and The Tarantula Nebulamentioning
confidence: 99%
“…Black solid lines are bonn evolutionary tracks and ZAMS(Brott et al 2011;Köhler et al 2015). The grey shaded contours visualise the predicted binary stellar population from BPASS(Eldridge et al 2017;Stevance et al 2020) for the observed age range. Each contour represents an order of magnitude difference in stellar number density.…”
mentioning
confidence: 99%
“…Analysis of these models made use of the pandas data frames of the BPASS models (Stevance 2020), which were constructed by the Python package(Stevance et al 2020a) …”
mentioning
confidence: 99%
“…Riroriro has been used for research in conjunction with BPASS, a suite of computer programs that simulates the evolution of a population of binary and single-star systems from a wide range of initial conditions and predicts their electromagnetic spectral emission (Eldridge et al, 2017;Stanway & Eldridge, 2018). There is also a Python interface for BPASS called Hoki (Stevance et al, 2020). This research took rates of formation of merging systems from BPASS and then evaluated the detectability of the gravitational wave signals from those systems using Riroriro.…”
Section: Researchmentioning
confidence: 99%